Pregunta
upstudy study bank question image url

10. Demonstrate and explain how to find the derivative of the following functions. Be sure to explicitly denote which derivative rules (scalar multiple, sum/difference, quotient, etc.) you are using in your work. (b) \[ f(y)=-\frac{3 y^{2}+5 y-3}{y^{3}} \]

Ask by Lowe Chavez. in the United States
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

To find the derivative of \( f(y) = -\frac{3y^{2} + 5y - 3}{y^{3}} \), follow these steps: 1. **Simplify the Function**: \[ f(y) = -\frac{3y^{2} + 5y - 3}{y^{3}} = -\left(3y^{-1} + 5y^{-2} - 3y^{-3}\right) \] 2. **Differentiate Term by Term Using the Power Rule**: - \( \frac{d}{dy}(-3y^{-1}) = 3y^{-2} \) - \( \frac{d}{dy}(-5y^{-2}) = 10y^{-3} \) - \( \frac{d}{dy}(3y^{-3}) = -9y^{-4} \) 3. **Combine the Derivatives**: \[ f'(y) = 3y^{-2} + 10y^{-3} - 9y^{-4} \] Alternatively, expressed with positive exponents: \[ f'(y) = \frac{3y^{2} + 10y - 9}{y^{4}} \] **Final Answer**: \[ f'(y) = 3y^{-2} + 10y^{-3} - 9y^{-4} \quad \text{or} \quad f'(y) = \frac{3y^{2} + 10y - 9}{y^{4}} \]

Solución

We wish to differentiate   f(y) = – (3y² + 5y – 3) / y³. One convenient strategy is to simplify f(y) first and then differentiate term by term using the power rule. We will also note along the way which rules are being used (constant multiple rule, sum/difference rule, and power rule). Step 1. Simplify the Function Recall that division by y³ allows us to rewrite each term:   (3y²)/y³ = 3y²⁻³ = 3y⁻¹,   (5y)/y³ = 5y¹⁻³ = 5y⁻²,   (–3)/y³ = –3y⁻³. Thus,   f(y) = –[3y² + 5y – 3] / y³      = –(3y² / y³ + 5y / y³ – 3/y³)      = –(3y⁻¹ + 5y⁻² – 3y⁻³). Distribute the negative sign:   f(y) = –3y⁻¹ – 5y⁻² + 3y⁻³. Step 2. Differentiate Term by Term We now differentiate each term using the power rule. Recall that the power rule states that d/dy (yⁿ) = n yⁿ⁻¹, and we also apply the constant multiple rule. 1. Differentiate –3y⁻¹:   d/dy [–3y⁻¹] = –3 · d/dy (y⁻¹)           = –3 · (–1)y⁻²                     [Power rule]           = 3y⁻². 2. Differentiate –5y⁻²:   d/dy [–5y⁻²] = –5 · d/dy (y⁻²)           = –5 · (–2)y⁻³                     [Power rule]           = 10y⁻³. 3. Differentiate 3y⁻³:   d/dy [3y⁻³] = 3 · d/dy (y⁻³)           = 3 · (–3)y⁻⁴                     [Power rule]           = –9y⁻⁴. Now, summing these results using the sum rule we obtain:   f′(y) = 3y⁻² + 10y⁻³ – 9y⁻⁴. Step 3. Express the Derivative in Fraction Form (Optional) Since y⁻² = 1/y², y⁻³ = 1/y³, and y⁻⁴ = 1/y⁴, we can rewrite the derivative as:   f′(y) = 3/y² + 10/y³ – 9/y⁴. For a common denominator, note that:   3y⁻² = 3y²/y⁴, 10y⁻³ = 10y/y⁴, –9y⁻⁴ = –9/y⁴. Thus,   f′(y) = (3y² + 10y – 9) / y⁴. Conclusion: We have used the constant multiple rule, the sum/difference rule, and the power rule to differentiate f(y). The final answer is:   f′(y) = 3y⁻² + 10y⁻³ – 9y⁻⁴  or   f′(y) = (3y² + 10y – 9) / y⁴.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To find the derivative of \( f(y) = -\frac{3y^2 + 5y - 3}{y^3} \), we can use the quotient rule, which states that if you have a function that is the quotient of two functions \( u(y) \) and \( v(y) \), then \[ f'(y) = \frac{u'v - uv'}{v^2}. \] Here, let \( u(y) = -(3y^2 + 5y - 3) \) and \( v(y) = y^3 \). First, we calculate \( u' \) and \( v' \): - \( u' = - (6y + 5) \) - \( v' = 3y^2 \) Now substituting into the quotient rule: \[ f'(y) = \frac{(-6y - 5)(y^3) - (-(3y^2 + 5y - 3))(3y^2)}{(y^3)^2}. \] After simplifying the numerator and denominator, we find \( f'(y) \). Remember to always simplify where possible! The derivative can often lead to a tidier final function that's easier to analyze or use in further calculations.

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad